Combination of LC‐Q‐TOF‐MS/MS, network pharmacology, and nanoemulsion approaches identifies active compounds of two Artemisia species responsible for tackling early diabetes‐related metabolic complications in the liver. Issue 7 (6th July 2022) - Moulahoum, Hichem; Ghorbanizamani, Faezeh; Khiari, Zineb; Toumi, Mohamed; Benazzoug, Yasmina; Timur, Suna; Zihnioglu, Figen
Abstract: Introduction: The chronicity of advanced glycation end‐products (AGEs) imparts various damages resulting in metabolic dysfunction and diseases involving inflammation and oxidative stress. The use of plant extracts is of high interest in complementary medicine. Yet, extracts are multicomponent mixtures, and difficult to pinpoint their exact mechanism. Objectives: We hypothesise that network pharmacology and bioinformatics can help experimental findings depict the exact active components and mechanism of action by which they induce their effects. Additionally, the toxicity and variability can be lowered and standardised with proper encapsulation methods. Methodology: Here, we propose the formulation of phytoniosomes encapsulating two Artemisia species ( Artemisia dracunculus and Artemisia absinthium ) to mitigate AGEs and their induced cell redox dysregulation in the liver. Extracts from different solvents were identified via liquid chromatography quadrupole time‐of‐flight mass spectrometry (LC‐Q‐TOF‐MS/MS). Phytoniosomes were explored for their anti‐glycating effect and modulation of AGE‐induced damages in THLE‐2 liver cells. Network pharmacology tools were used to identify possible targets and signalling pathways implicated. Results: Data demonstrated that A. absinthium phytoniosomes had a significant anti‐AGE effect comparable to reference molecules and higher than A. dracunculus . They were able to restore cell dysfunction through the restoration of tumour necrosis alpha (TNF‐α), interleukin 6 (IL‐6), nitric oxide, and total antioxidant capacity. Phytoniosomes were able to protect cells from apoptosis by decreasing caspase 3 activity. Network pharmacology and bioinformatic analysis confirmed the induction of the effect via Akt‐PI3K‐MAPK and AGE‐RAGE signalling pathways through quercetin and luteolin actions. Conclusion: The current report highlights the potential of Artemisia phytoniosomes as strong contenders in AGE‐related disease therapy. Abstract : Two Artemisia plant extracts' applications in diabetes‐related liver diseases are studies by combining experimental and bioinformatic tools. Luteolin and quercetin as the majorcompounds induce their effect through advanced glycation end‐product (AGE)‐receptor of AGEs (RAGE) and Akt‐PI3K‐MAPK pathways according to network pharmacology analyses. Phytoniosomes are prepared in order to standardise plant‐based treatments and lower toxicity. The approach protects the liver from AGE‐induced diabetes‐related cell damages and prevents inflammatory cytokines and apoptosis regulation.